Synthesis of reduced graphene oxide-montmorillonite nanocomposite and its application in hexavalent chromium removal from aqueous solutions1. Issue 59 (28th June 2015) - Zhang, Zilong; Luo, Hanjin; Jiang, Xiaolu; Jiang, Zhongjie; Yang, Chen
<x xml:space="preserve">Abstract</x> The combination of Mt and rGO protect rGO from aggregation.